Impact of Demonetization on Real Estate Business ofHaryana - Amanpreet (Gyan Management Journal, 2018)
With the purpose of controlling the black money the decision of demonetization was made on 8th of November, 2016 which is expected to have immediate effects on various sectors of India namely as service sector, transportation section and agriculture sector. The notes of Rs. 500 and 1000 considered as the illegal denominations and the decision was made to deposit all the denominations of Rs.500 and 1000 in banks. The aim of the study is to determine the impact of demonetization on the real estate business with the special reference to Haryana state. Various factors such are the prices, interest rates and manufacturing activities of real estate businesses are taken into consideration and analyzed with the purpose of measuring the impacts of demonetization on these selected factors. To satisfy the objectives of the research study responses are collected from 138 respondents and the collected data was analyzed with the help of SPSS.16 by using the ANNOVA technique. The results revealed that demonetization has significant impact on price, interest rates and manufacturing activities of real estate businesses. This research study will give the true picture of real estate investors and help them to make the investment decisions related to the buying and selling of the land and properties in a profitable manner.
Keywords: Demonetization; Real estate business; Owners and Dealers